Exploring the nexus between water saving and energy conservation: Insights from industry sector during the 12th Five-Year Plan period in China. (June 2016) - Gu, Alun; Teng, Fei; Lv, Zhiqiang
Abstract: China׳s 12th Five-Year Plan, released in March 2011, specifies water management targets in addition to energy and carbon intensity targets. Energy and water resources are becoming the major bottlenecks restricting sustainable development in China. Energy and water are interconnected and complementary; however, macroenergy policies do not consider the impact on water resources, while water related policies do not consider the impact on energy consumption. In this paper, an energy-water evaluation methodology based on an input–output model was introduced, and correlation between energy and water supply sectors was established by this methodology. The correlation coefficients for the energy-water nexus, allowing the water savings associated with energy saving policies in China to be estimated, particularly for key industrial sectors during the 12th Five-Year Plan period were provided. These results indicate that by achieving the energy saving targets in the end of the 12th Five-Year Plan, progress will also be made toward achieving the water use targets. It is believed that targets for the synergies between energy savings and water conservation should be improved. The effect of water conservation resulting from energy savings varies greatly in different sectors, and to maximize the synergies, energy and water conservation technologies should be promoted in key industrial sectors.